Promoting physical activity among socially disadvantaged women: Findings on target group outreach, course retention, and impact of the BIG project as a case study for participatory interventions in community settings Bewegungsförderung bei sozial benachteiligten Frauen: Erkenntnisse zur Zielgruppenerreichung, Kursbindung und Wirkung des BIG-Projekts als Fallstudie für partizipative Interventionen im kommunalen Setting - Linder, Stephanie; Herbert-Maul, Annika; Ziemainz, Heiko; Thiel, Ansgar; Holle, Rolf; Laxy, Michael; Pedron, Sara; Abu-Omar, Karim (German Journal of Exercise and Sport Research, 2023)
Background: The BIG project—a participatory project in a community setting (“Bewegung als Investition in Gesundheit”)—was developed in 2005 to facilitate access to physical activity for disadvantaged women. Since then, BIG has been transferred to 17 municipalities. Aim: To investigate whether socially disadvantaged women can be reached and retained in exercise classes in the BIG project. In addition, the information provided by the women on their state of health and exercise is reported. Finally, we will examine whether five risk factors associated with social disadvantages are associated with health status and physical activity. Methods: Quantitative cross-sectional data from six survey waves (2006–2013) from two project sites (Erlangen, Regensburg) were summarized. To analyze the reach of the target group, participant characteristics (N = 430) were compared with population data from the sites. The reach of the target group, course retention, and data on health status and physical activity were also descriptively analyzed. The influence of risk factors and physical activity on health status was examined by multivariate regression analyses. Results: Of the participants, 67% had at least one risk factor. Women participated in the BIG courses for a mean of 2.4 years. Over 50% of women reported improved health, and over 60% exercised more compared with before BIG. The number of risk factors present was associated with the health status compared to the time before BIG (p < 0.001). Lack of German language skills showed a significant association with current health status. Conclusions: The BIG project reaches socially disadvantaged women. In particular, women with few risk factors report positive change in health status and physical activity compared to the time before BIG participation. Here, the number of risk factors present and lack of German language skills seem to be important.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Health promotion; Participation; Physical activity promotion; Socioeconomic disparities in health; Target group reach